2003
DOI: 10.1079/bjn2003825
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial infarction risk in relation to zinc concentration in toenails

Abstract: Zn is an essential mineral. The role of Zn in atherosclerosis is not clear. Epidemiological studies, which have reported contradictory results, are limited by the use of serum Zn levels as a marker of intake. We assessed the association of toenail Zn, which integrates dietary Zn intake over 3 to 12 months, with the risk of a first myocardial infarction. Toenail Zn concentrations were determined by neutron activation analysis in the European multi-centre case -control study on antioxidants, myocardial infarctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 22 publications
3
17
0
Order By: Relevance
“…First, there were 10 case-control studies to measure the toenail Zn level which was inconsistent with the serum and hair Zn level, and all these case-control studies were from the study performed by Martin-Moreno in 2003. Thus, the inconsistency of the results of subgroup analyses stratified by sample specimen was caused by the study of Martin-Moreno (2003).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…First, there were 10 case-control studies to measure the toenail Zn level which was inconsistent with the serum and hair Zn level, and all these case-control studies were from the study performed by Martin-Moreno in 2003. Thus, the inconsistency of the results of subgroup analyses stratified by sample specimen was caused by the study of Martin-Moreno (2003).…”
Section: Discussionmentioning
confidence: 95%
“…And the difference of Zn levels between MI and healthy controls in Asia was greater to that among the population in Europe, but no difference was found in Oceania. And we found that the inconsistency of the results of subgroup analyses might be caused by a study of Martin-Moreno (2003). First, there were 10 case-control studies to measure the toenail Zn level which was inconsistent with the serum and hair Zn level, and all these case-control studies were from the study performed by Martin-Moreno in 2003.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The prostate gland hazard does not grow when the content of cadmium in toe-nails increases and does not decay when the zinc content increases. Martin-Moreno et al (2003) investigated the correlation between the zinc content in toenails and the hazard of cardiac infarct in European population. The authors have shown that the zinc content in nails of sick people differs slightly (slightly is not an analytical expression) from that in nails of healthy people.…”
Section: Introductionmentioning
confidence: 99%